Molecular characterization and expression analysis of Mtmr2, mouse homologue of MTMR2, the Myotubularin-related 2 gene, mutated in CMT4B. - Bolino, A; Marigo, V; Ferrera, F; Loader, J; Romio, L; Leoni, A; Di Duca, M; Cinti, R; Cecchi, C; Feltri, M; Wrabetz, L; Ravazzolo, R; et al. (2002)
Charcot-Marie-Tooth type 4B (CMT4B) is caused by mutations in the myotubularin-related 2 gene, MTMR2, on chromosome 11q22. To date, six loss of function mutations and one missense mutation have been demonstrated in CMT4B patients. It remains to be determined how dysfunction of a ubiquitously expressed phosphatase causes a demyelinating neuropathy. An animal model for CMT4B would provide insights into the pathogenesis of this disorder. We have therefore characterized the mouse homologue of MTMR2 by reconstructing the full-length Mtmr2 cDNA as well as the genomic structure. The 1932 nucleotide open reading frame corresponds to 15 coding exons, spanning a genomic region of approximately 55 kilobases, on mouse chromosome 9 as demonstrated by fluorescence in situ hybridization analysis. A comparison between the mouse and human genes revealed a similar genomic structure, except for the number of alternatively spliced exons in the 5'-untranslated region, two in mouse and three in man. In situ hybridization analysis of mouse embryos showed that Mtmr2 was ubiquitously expressed during organogenesis at E9.5, with some areas of enriched expression. At E14.5, Mtmr2 mRNA was more abundant in the peripheral nervous system, including in dorsal root ganglia and spinal roots.